1980
DOI: 10.1111/j.1471-4159.1980.tb04630.x
|View full text |Cite
|
Sign up to set email alerts
|

Gangliosides of Human Cerebral Astrocytomas

Abstract: Ganglioside content and composition were examined in a series of 25 human gliomas, which were graded histologically by the criteria of Kernohan. The concentration of total gangliosides (lipid-bound sialic acid [LBSA]) was decreased with respect to normal brain tissue in nearly all tumors, and the extent of reduction correlated with the stage of tumor anaplasia. The distribution of individual gangliosides was altered in glial tumor tissue with an increase in proportion of the structurally simple gangliosides an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
52
0

Year Published

1980
1980
2014
2014

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 109 publications
(55 citation statements)
references
References 34 publications
3
52
0
Order By: Relevance
“…Another important factor contributing to the difference in therapeutic efficacy may be the expression level of sialic acids. The receptor for SeV is sialic acid bound to gangliosides, which is present on most cell types including the human glia and glioma cells (22,23). It may be altered by infiltration of the host cells in the xenograft models (24) and this probably affects the infection efficiency of hIL2-SeV/DMDF and resultant efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…Another important factor contributing to the difference in therapeutic efficacy may be the expression level of sialic acids. The receptor for SeV is sialic acid bound to gangliosides, which is present on most cell types including the human glia and glioma cells (22,23). It may be altered by infiltration of the host cells in the xenograft models (24) and this probably affects the infection efficiency of hIL2-SeV/DMDF and resultant efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…This is a major ganglioside of neuroblastoma tissue, 15,16 comprising up to 28% of the total gangliosides of this tumour, 16 and it is found in other tumours of neuroectodermal origin. [17][18][19][20] Tumour-derived gangliosides whose carbohydrate structures are the same as those of gangliosides of normal tissues such as brain may nevertheless show minor differences in the ceramide (lipid) portion of the molecule. 21 Therefore, the complete molecular characterisation of the neuroblastoma-associated ganglioside described here will be of interest.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that human glioma biopsies show elevation of monosialylated GM3 and GM2 and their disialylated derivatives GD3 and GD2 (12)(13)(14). The increase of GD3 was most significant, but the correlation between GD3 and malignancy remains obscure (15,16).…”
mentioning
confidence: 99%